ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI KONSUMEN PADA SITUS JUAL-BELI ONLINE - Setiawan, I Gede Andri; Sukardi, Sukardi (Jurnal Fokus Manajemen Bisnis, 2016)
The purpose of this study were to analyze (1) the influence of trust of the purchase interest of online shop consumers, (2) the influence of risk perception of the  purchase  interest  of  online  shop  consumers,  (3)  the  influence  of  use fulness perception of the purchase interest of online shop consumers, (4) the influence of price perception of the purchase interest of online shop consumers. The populations in this research are  student of Ahmad Dahlah University Yogyakarta  Campus  One.  The  method  sample  is  purposif  sampling  with  the number  of  sample  as  much  as  100  respondents  from  three  Faculty  that  is, Economy  Faculty,  Psycology  Faculty,  and  FTDI.  Collecting  data  using questionnaires  that  was  done  validity  test  and  realibity  test.  This  research  was done by using multiple linear regression data analysis. The  results  of  this  study  indicate  that  (1)  the  trust  is  not  significant influence on consumer purchase interest of the sites online shop, this is evidenced by the significant value  is bigger  than the probability alpha value of 0.05 (0,206 > 0.05), and the regression coefficient has a  positive value of 0.062; (2)  the  trust is not significant influence on consumer purchase interest of the sites online shop, this  is  evidenced  by  the  significant  value  is  bigger  than  the  probability  alpha value of 0.05 (0, 0,234 > 0.05), and the regression coefficient has a positive value of  0.057;  (3)  the  usefulness  perception  is  significant  influence  on  consumer purchase interest of the sites online shop, this is evidenced by the significant value is  smaller  than  the  probability  alpha  value  of  0.05  (0.000  <  0.05),  and  the regression coefficients has a positive value of 0.456; (4) the price perception is not significant  influence on consumer purchase interest of the sites online shop, this  is  evidenced  by  the  significant  value  is  bigger  than  the  probability  alpha value of 0.05 (0.066 > 0.05), and the regression coefficient has a  positive value of  0.111;  and  (5)  trust,  risk  perception,  usefulness  perception  and  price perception  together  have  an  effect  on  consumer  purchase  interest  of  the  sites online  shop,  this  is  evidenced  by  the  significant  value  is  smaller  than  the probability alpha value of 0.05 (0.000 < 0.05). The R2 test results in this study was obtained  R2 value  of  0.413.  This  shows  that  purchase  interest  is  influenced  by trust, risk perception, use perception, and price  perception by 41.3%, while the remaining 58.7% is influenced by other factors not observed by the researcher or considered fixed.